2012
DOI: 10.4318/tjg.2012.0310
|View full text |Cite
|
Sign up to set email alerts
|

Serum complement C4 in chronic hepatitis C: Correlation with histopathologic findings and disease activity

Abstract: Amaç: Hepatit C virüsü kronik karaci¤er hastal›¤›, siroz ve hepatosellüler kansere neden olmaktad›r. Kronik hepatit C'nin tan› ve takibinde kullan›lan viral marker ve laboratuvar testleri hastal›¤›n aktivitesi ve karaci¤er histopatolojik bulgular›yla iyi korelas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…According to the proteomic analysis of patients with chronic hepatitis C virus infection, some researchers revealed that complement C4a could be a candidate to predict liver fibrosis . Other researchers also found that serum complement C4 level was significantly correlated with histological activity in CHC patients . Though a few studies focused on the influence of complement C4a on HBV infection patients at present, those scholars paid attention to C4 gene and identified that C4 gene deletions were associated with nonresponse of the virus to hepatitis B vaccine .…”
Section: Discussionmentioning
confidence: 99%
“…According to the proteomic analysis of patients with chronic hepatitis C virus infection, some researchers revealed that complement C4a could be a candidate to predict liver fibrosis . Other researchers also found that serum complement C4 level was significantly correlated with histological activity in CHC patients . Though a few studies focused on the influence of complement C4a on HBV infection patients at present, those scholars paid attention to C4 gene and identified that C4 gene deletions were associated with nonresponse of the virus to hepatitis B vaccine .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a cross-sectional study suggested that plasma C3 levels are associated with liver fat and paralleled the degree of liver injury (Wlazlo et al 2013). Compared with those with normal transaminase levels, serum C3 and C4 levels in patients with high transaminase levels were significantly lower (Bugdaci et al 2012). Moreover, we previously found that C3 and C4 were associated with the risk of MetS (Liu et al 2016), which is one of the risk factors of NAFLD.…”
Section: Introductionmentioning
confidence: 90%
“…In this study, we determined significant AUC values between noninvasive tests in the literature regarding patients with hepatitis C. However, why different AUC values are obtained in patients with CHB and in patients with CHC despite the similarities in grades and stages is a matter of debate. Although patients with hepatitis B and C present with similar histopathological findings and are evaluated with the same scoring system, the observation of marked hepatosteatosis in patients with CHC (22) and the presence of inflammatory destruction and complementary activity suggest to us that different ultrastructural mechanisms may play a role (5,25).…”
Section: Discussionmentioning
confidence: 99%